Strategi Gerakan Pengumpulan Kotak Infaq Nahdlatul Ulama di LazisNU Metro Selatan Lampung - Mulan Erniati; Ahmad Muslimin; Finny Ligery (Bulletin of Indonesian Islamic Studies, 2024)
This research aims to analyze the fundraising strategy employed by LazisNU South Metro through the KOIN NU initiative, which focuses on the infaq socialization system. It also explores the supporting and inhibiting factors related to this movement. The study utilizes a descriptive method with a qualitative approach, gathering data through observation, interviews, and documentation. Qualitative data analysis encompasses several stages, including data reduction, data presentation, and the drawing of conclusions/verification. This process systematically organizes, simplifies, presents, and interprets the data to uncover meaningful insights and relevant patterns. The findings highlight two critical points. First, the success of this program is contingent upon effective planning that incorporates specific targets, thorough socialization, and transparent management practices. Regular briefings aimed at motivating field officers and fostering community participation are also essential. Second, systematic supervision and active donor involvement enhance transparency and accountability. Nevertheless, challenges persist, such as a lack of dedicated managers and administrators who are not sufficiently focused on the program's management. Addressing these challenges is crucial for improving overall effectiveness.